Riggs’ Prismatic Model & its Application in Nepal’s Public Administration - Sarma Prasain, Pradip (Medha: A Multidisciplinary Journal, 2025)
This study endeavors to examine Fred W. Riggs' Prismatic model within the framework of Nepal's contemporary public administration and democratic system. It analyses the discrepancy between the ideals of democracy and the reality of governance in the Nepali experience, which began after the fall of the Rana autocracy in 1951. With the use of qualitative methods, interpretive techniques, and a systematic review of scholarly literature, the study identifies Riggs' model as a key theoretical foundation in comparative public administration for studying developing administrative structures and processes. The research conceptualizes Nepal as a prismatic society, wherein traditional norms and modern administrative practices coexist, generating institutional hybridity and structural overlap. Despite a history of democratic reforms, including the establishment of a federal republic under the 2015 Constitution, Nepal remains, as Riggs posited, in a transitional phase. Structural imbalances, such as hierarchical rigidity, weak institutional capacity, nepotism, and favoritism, have produced administrative instability and inefficiency. Key features of the prismatic model, including heterogeneity, formalism, and overlapping functions, are evident as formal democratic institutions are often undermined by informal patronage networks and socio-cultural expectations. This hybridity erodes public trust in governance. Riggs' prismatic model thus becomes a critical analytical instrument to examine Nepal's political-administrative development and the persistent challenges in achieving a fully integrated, transparent, and accountable society. Unchecked nepotism, patronage, and corruption in Nepal’s administration will inevitably deepen the nation’s crisis, eroding public trust, stalling development, and damaging its global standing.